Antiproliferative activity of Curcusone B from Jatropha Curcas on human cancer cell lines - Sahidin,; Nakazibwe, Sauba; Taher, Muhammad; Kumar Saxena, Anil; Arief Ichwan, Solachuddin Jauhari; Ardiyansyah, (INSI Publications, 2011)
This study was designed to determine antiproliferative properties of curcusone B from the stem bark of Jatropha curcas on cell lines K562 (chronic myelogeneous leukemia), and H1299 (human non-small cell lung carcinoma). Cells were cultured in the presence of curcusone B at various concentrations and the percentage of cell viability was evaluated by trypan blue exclusion method and MTT assay. Curcusone B showed significant dose-dependent inhibition of cell proliferation of K562 and H1299 cell lines with an IC50 of 6 μg/mL and 15.0 μg/mL, respectively. The findings suggested that the curcusone B had strong antiproliferation which was dose dependent and may have potential as an anticancer agent.